THE ROLE OF MULTIMEDIA IN ENHANCING KNOWLEDGE REPRESENTATION AND LEARNING OUTCOMES IN TRANSLATION EDUCATION - Pramawati, Anak Agung Istri Yudhi; Mantra, Ida Bagus Nyoman; Pramerta, I Gde Putu Agus (English Review: Journal of English Education, 2025)
The application of multimedia in translation education enhances learning and knowledge representation. In this research, the application of animated video, infographic, and gamified translation application is applied to enhance students' performance and engagement in translation study. Using qualitative ethnographic strategies, including classroom observation and interviews, the study explores how multimedia technologies support translation learning. Results show that animated videos successfully visualize complicated translation techniques, text analysis, and cultural adaptation so that abstract theories become more clear. Infographics offer step-by-step, systematically organized descriptions of translation processes for reinforcement of learners' understanding. Gamified programmed like Duolingo and FluentU encourage active translation practice on the part of learners, while motivating them with fun activities and games. While these benefits are present, the study quotes challenges such as cognitive overload and surface learning danger in the event multimedia tools are not accompanied by structured instruction. The results emphasize the need for a balanced pedagogical approach, combining multimedia with conventional text-based instruction and discussion-based methods to maximize engagement and critical thinking.This research contributes to the discussion of multimedia in translation education, highlighting its pedagogical potential and limitations. Subsequent studies should explore the long-term impact of multimedia on translation ability and its adaptability in different learning settings